Population factors predicting survival in breast cancer: analysis according to the data of the Arkhangelsk Regional Cancer Registry in 2000–2020 - A. V. Agaeva; A. V. Svetlakova; D. D. Gromov; O. V. Chemakina; L. E. Valkova; A. A. Dyachenko; D. V. Bogdanov; M. Yu. Valkov (Опухоли женской репродуктивной системы, 2023)
Background. Breast cancer (BC) is the leading cancer in the world and in Russia. Epidemiological factors predicting breast cancer survival in Russia have not been studied enough.   Aim. To evaluate the factors predicting survival in BC by the data of the Arkhangelsk Regional Cancer Registry in 2000–2020 and the survival during the COVID-19 pandemic   Materials and methods. Data on all cases of Вс for 2000–2020 retrieved from the Arkhangelsk Regional Cancer Registry database. Cancer-specific survival was estimated using the Kaplan–Meier and the life tables method. The prognostic value of variables available in Arkhangelsk Regional Cancer Registry was assessed in Cox regression.   Results. The final analysis included 9,089 cases of breast cancer. During the observation period, 2723 deaths from breast cancer were registered. The one-, five- and ten-year survival rates in the entire population were 91.6 %, 73.0 % and 64.0 %, respectively. In a multivariate analysis, the risk of death from BC increased by 2.9, 8.2, 21.3 and 6.8 at 2, 3, 4 and unknown stages; 2.1 times with the localization of the tumor in the area of the nipple and areola; by 33 % in ductal cancer compared with lobular cancer, by 1.8 and 2.6 times in those who received palliative treatment and did not receive treatment; by 33 % in women aged 80 years and older; by 22 % for those living in rural areas. In the period 2013–2019, the 5-year cancer-specific survival reached 79.1 %, which is 14 % and 6 % higher than in the periods 2000–2006 and 2007–2012. Survival rates have not declined during the COVID-19 pandemic.   Conclusion. The risk of death from BC is increased in advanced stages, ductal morphology, localization in the nipple-areolar region, age over 80 years, and living in rural areas. During the COVID-19 pandemic BC survival did not worsen, but this requires further study.